PRADA: Portable Reusable Accurate Diagnostics with nanostar Antennas for multiplexed biomarker screening. Issue 3 (15th May 2020) - Wen, Xiaona; Ou, Yu‐Chuan; Zarick, Holly F.; Zhang, Xin; Hmelo, Anthony B.; Victor, Quinton J.; Paul, Eden P.; Slocik, Joseph M.; Naik, Rajesh R.; Bellan, Leon M.; Lin, Eugene C.; Bardhan, Rizia
Abstract: Precise monitoring of specific biomarkers in biological fluids with accurate biodiagnostic sensors is critical for early diagnosis of diseases and subsequent treatment planning. In this work, we demonstrated an innovative biodiagnostic sensor, portable reusable accurate diagnostics with nanostar antennas (PRADA), for multiplexed biomarker detection in small volumes ( 50 μl) enabled in a microfluidic platform. Here, PRADA simultaneously detected two biomarkers of myocardial infarction, cardiac troponin I (cTnI), which is well accepted for cardiac disorders, and neuropeptide Y (NPY), which controls cardiac sympathetic drive. In PRADA immunoassay, magnetic beads captured the biomarkers in human serum samples, and gold nanostars (GNSs) "antennas" labeled with peptide biorecognition elements and Raman tags detected the biomarkers via surface‐enhanced Raman spectroscopy (SERS). The peptide‐conjugated GNS‐SERS barcodes were leveraged to achieve high sensitivity, with a limit of detection (LOD) of 0.0055 ng/ml of cTnI, and a LOD of 0.12 ng/ml of NPY comparable with commercially available test kits. The innovation of PRADA was also in the regeneration and reuse of the same sensor chip for 14 cycles. We validated PRADA by testing cTnI in 11 de‐identified cardiac patient samples of various demographics within a 95% confidence interval and high precision profile. We envision low‐cost PRADA will have tremendous translational impact and be amenable to resource‐limited settings for accurate treatment planning in patients.